Synthesis, Physico-Chemical Characterization, and Cytotoxicity Assay of Mannich Base Derivatives with Heavy Metal Ions on RAW 264.7 Cell Line - Mahasin Alias (Journal of Global Pharma Technology, 2018)
Heavy metal complexes of Pd (II), Pt(IV) and Au (III) with new ligands of mannich base S-(1-(benzothiazole-2-ylamino)methyl]-H-benzimidazole-2-yl]4-nitrobenzothioate as (L1), S-(1-((pyra- zine-2-carboxamido)methyl)-1-H-benzoimidaz-ole-2-yl)4-nitrobenzothioate as (L2) & S-(1-Morph- olinomethyl)-1-benzoimidazol-2-yl) 4-nitrobenzothioate as (L3) have been prepared and characterized in solid state, their most probable structure were established through a combination of different spectroscopic and analytical techniques such as: elemental analysis C.H.N.S, flame atomic absorption (A.A), FT-IR, UV–vis spectrophotometry, 1H13CNMR, as well as conductivity and magnetic susceptibility measurements. The ratio of M:L and stability constant was determined by using molar ratio method in solution state. From the spectral studies, an octahedral geometry of PtL1, PtL2, AuL2, PtL3, PdL3 & AuL3 complexes, while PdL1, AuL1 & PdL2 have square planner geometry. Cytotoxic effect of prepare ligands and their novel complexes were evaluated against RAW 264.7 cell line by using four different concentrations (400, 200, 100 & 50µg/ml) in exposure time 48 hrs. and compared this effect with control positive Cis-Pt.Keywords: Mannich base, Benzimidazole, Analytical techniques, Cytotoxic, Exposure time.